Graphene Acoustic Phonon‐Mediated Pseudo‐Landau Levels Tailoring Probed by Scanning Tunneling Spectroscopy. Issue 2 (9th December 2019) - Chi, Cheng; Shi, Bowen; Liu, Cong; Kang, Yimin; Lin, Li; Jiang, Meiling; Lu, Jing; Shen, Bo; Lin, Feng; Peng, Hailin; Fang, Zheyu
Abstract: Graphene has attracted great interests in various areas including optoelectronics, spintronics, and nanomechanics due to its unique electronic structure, a linear dispersion with a zero bandgap around the Dirac point. Shifts of Dirac cones in graphene creates pseudo‐magnetic field, which generates an energy gap and brings a zero‐magnetic‐field analogue of the quantum Hall effect. Recent studies have demonstrated that graphene pseudo‐magnetic effects can be generated by vacancy defects, atom adsorption, zigzag or armchair edges, and external strain. Here, a larger than 100 T pseudo‐magnetic field is reported that generated on the step area of graphene; and with the ultrahigh vacuum scanning tunneling microscopy, the observed Landau levels can be effectively tailored by graphene phonons. The zero pseudo‐Landau level is suppressed due to the phonon‐mediated inelastic tunneling, and this is observed by the scanning tunneling spectroscopy spectrum and confirmed by the Vienna ab initio simulation package calculation, where graphene phonons modulate the flow of tunneling electrons and further mediate pseudo‐Landau levels. These observations demonstrate a viable approach for the control of pseudo‐Landau levels, which tailors the electronic structure of graphene, and further ignites applications in graphene valley electronics. Abstract : Pseudo‐magnetic field at the order of 100 T is obtained at Cu steps vicinity, which is illustrated by analyzing peaks in scanning tunneling spectra corresponded to pseudo‐Landau levels. Furthermore, tailoring pseudo‐Landau levels is realized by introducing phonon‐mediated inelastic tunneling, which is confirmed by scanning tunneling spectra and Vienna ab initio simulation package simulations, thus opens up another dimension in mediating graphene electronic structure.